2019
DOI: 10.1002/14651858.mr000050
|View full text |Cite
|
Sign up to set email alerts
|

Placebo, usual care and wait-list interventions for all mental health disorders

Abstract: This is a protocol for a Cochrane Review (Methodology). The objectives are as follows: Our objectives are to assess the beneficial effects and adverse events of placebos, usual care, and wait-list interventions for all mental health disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Accordingly, the effect sizes for studies with wait-list control designs may have been artificially inflated. A better understanding of the influence of control conditions on treatment effects should be a focus of future research to develop empirical guidelines that aim to optimize the design of future RCTs …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the effect sizes for studies with wait-list control designs may have been artificially inflated. A better understanding of the influence of control conditions on treatment effects should be a focus of future research to develop empirical guidelines that aim to optimize the design of future RCTs …”
Section: Discussionmentioning
confidence: 99%
“…Despite promising early evidence, only 20% of randomized controlled trials (RCT) studies on selective preventions include some active control condition (ACC) [ 11 ]. The use of waitlist control conditions (WLCs) in RCTs may also overestimate treatment effects and thus artificially inflate the effect sizes of prevention programs [ 1 , 26 , 31 , 36 , 74 ]. Further, it is suggested that the positive effects diminish over time [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…• Studies using as a control condition one of the following: treatment / care as usual, wait-list, active control, and placebo. In keeping with standard definitions used by the Cochrane database (Faltinsen et al, 2019), usual care was defined as an intervention that reflects locally accepted treatment practices for individuals with bipolar disorder. Wait list was defined as receiving the experimental intervention after the trial ended.…”
Section: Eligibility Criteriamentioning
confidence: 99%